The Effect of Papaya Leaf Extract (Carica papaya L.) on the Mortality Rate of Spodoptera litura Fabricius Larvae and the Level of Damage to Soybean Leaves in Malang, Indonesia: A Greenhouse Simulation - Sofia Ery Rahayu; Amin Setyo Leksono; Zulfaidah Penata Gama; Hagus Tarno (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Spodoptera litura Fabricius pest control using botanical pesticide from papaya leaves extract (PLE) is an alternative to substitute chemical pesticides. The study aimed to determine the levels of PLE's activity and evaluate the effectiveness of PLE from different altitudes (low and middle lands) and cultivars (Thailand and Indonesian) against the attack of S. litura Fabricius larvae. An experimental study with a randomized block design (n=5) was conducted from December 2020 until April 2021. Each replication used 100 soybean plants and sprayed with 0% or 20% PLE of Indonesian purple cultivar low land (UR-20%), Indonesian purple cultivar middle land (US-20%), Thailand cultivar low land (TR-20%), and Thailand cultivar middle land (TS-20%), respectively and observed at 72 hours after treatment. The results demonstrate that the middle lands contained active compounds slightly higher than the lowlands. The damaged soybean leaves and intensity of soybean leaf damage are highest in control (77% and 63%) and significantly different from the treatment group, 53-60% and 29-41%, respectively. The mortality of S. litura Fabricius larvae in the control group was 11%, and in the treatment group, 47-63%. PLE from different altitudes and cultivars reduce the intensity of soybean leaf damage by S. litura Fabricius larvae.